Tổng hợp vật liệu F-TiO2/Bent và đánh giá hoạt tính quang xúc tác trong vùng ánh sáng khả kiến - Diệu Cẩm, Nguyễn Thị (Vietnam Journal of Chemistry, 2017)
Flouride doped TiO2 loaded on bentonite support (F-TiO2/Bent) has been emerged as an effective catalyst for improving the activity of F-TiO2. F-doped TiO2/Bent material was prepared by sol-gel route from Binh Dinh ilmenite ore using KF as a dopant precursor. The experimental results revealed that F-TiO2/Bent material exhibited a quite unique spherical structure as compared to F-TiO2. The absorption in the visible light of the F-TiO2/Bent was found to be improved and was shifted to longer wavelength (visible region). Compared with F-TiO2, the as-prepared photocatalysts exhibit enhanced photocatalytic performance treatment of methylene blue (MB) under visible light. Keywords. Titanium dioxide, fluoride, bentonite, photocatalysis, visible light.